PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI PERKALIAN MELALUI METODE TURUS KELAS V MI KHOIRIYAH - Lina Nur Afifah; Damar Septian (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
This study examines the role of mathematics in fostering students’ critical, logical, and systematic thinking skills, with a particular focus on multiplication, a topic that many elementary students find difficult to understand. Initial observations in a Grade V classroom revealed that students’ learning outcomes in multiplication were unsatisfactory, as evidenced by a classical mastery level of only 50%. To address this problem, the study implemented the tally method, which provides a concrete and visual approach to learning multiplication through the use of intersecting lines representing multiplication factors. The research employed a Classroom Action Research (CAR) design consisting of one cycle with four stages: planning, action, observation, and reflection. The participants were Grade V students at a Madrasah Ibtidaiyah, while data were collected through learning outcome tests, classroom observations, and documentation. A mixed-method approach was used to analyze the data. The findings demonstrated that the tally method effectively improved students’ understanding and achievement in multiplication. Following the implementation of the instructional intervention, the percentage of students achieving mastery increased from 50% to 75%. These results suggest that the tally method enhances conceptual understanding by enabling students to visualize multiplication processes more concretely, thereby improving their engagement and overall learning outcomes.